Cutaneous histiocytic sarcoma with E-cadherin expression in a Pembroke Welsh Corgi dog. (September 2015) - Hirako, Ayano; Sugiyama, Akihiko; Sakurai, Masashi; Ozaki, Kiyokazu; Sakai, Hiroki; Takeuchi, Takashi; Morita, Takehito; Moore, Peter F.
An 11-year-old male neutered Pembroke Welsh Corgi dog displayed a mass measuring 7.5 cm × 6.6 cm × 1.6 cm in the skin. Neoplastic tissue was nonencapsulated, and the neoplastic cells showed infiltrative growth into the surrounding tissue on microscopic examination. The neoplastic tissue was mainly located from the dermis to the subcutis. Epidermotropism of neoplastic cells was not observed. The tissue was composed of irregular, solid nests of round to polygonal cells. Nests were separated by fine fibrovascular stroma. Mitotic index was high (7.90 ± 0.38 per high power field) and extensive necrosis was observed in the neoplastic tissue. Vascular invasion was often observed in the neoplastic tissue. Neoplastic cells were positive for vimentin, HLA-DR antigen, Iba1, CD18, and E-cadherin, but cells did not express cytokeratin, S100, CD20, CD79α, CD3, MUM-1, lambda light chain, kappa light chain, lysozyme, CD204, or CD11d by immunohistochemistry. Electron microscopic analysis revealed dendrites on these cells. From the above-mentioned findings, the tumor was diagnosed as a cutaneous histiocytic sarcoma with E-cadherin expression. It is possible that neoplastic cells in the present case were derived from cutaneous Langerhans cell. To our knowledge, cutaneous histiocytic sarcoma with E-cadherin expression in domestic animals has not been previously diagnosed in domestic animals.